THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE LABOR MARKET: CHANGES IN SUPPLY AND DEMAND - Suratova, Rukhsorakhon; Abdurazakova, Kamola (Journal of Fundamental Studies, 2026)
This article analyzes the impact of artificial intelligence technologies on the global labor market, particularly their influence on changes in the structure of labor supply and demand. The study examines the role of artificial intelligence and automation in the economy, the creation of new jobs, and the decline of certain occupations based on scientific literature and data from international organizations. In particular, the effects of artificial intelligence on labor markets in developed and developing countries are comparatively analyzed using reports from the International Monetary Fund and the Organisation for Economic Co-operation and Development. The findings indicate that artificial intelligence, on the one hand, contributes to the reduction of jobs based on low-skilled and routine tasks, while on the other hand increasing the demand for highly skilled professionals. The article also emphasizes the importance of developing human capital, modernizing the education system, and expanding reskilling and upskilling programs to ensure the sustainable development of the labor market in the future.